Withania somnifera : A Remarkable Herb to Improve Animal Fertility - Mittal, Nikita; Ranjan, Ravi; Bharadwaj, Alok (The Indian Journal of Animal Reproduction, 2025)
Since ancient times, herbal remedies have been utilized to treat male infertility, and in recent years, their usage has been gradually increasing. Research on the effectiveness of herbal remedies appears to be a resurgence of conventional medical methods. For more than three centuries, ashwagandha has been utilized in Ayurvedic and traditional medical systems. A rising number of human experiments are assessing ashwagandha efficacy under various situations, as a result of its growing popularity and interest in numerous Western countries. The majority of the results from these investiga tions suggested that consuming ashwagandha has benefits, despite large variations in treatment dosage, duration, and types of extract used. Overall, the reduction of stress and anxiety symptoms is the best proof of ashwagandha thera peutic effectiveness. The systematic review’s findings indicate that ashwagandha may have a wide range of medicinal uses. Ashwagandha is a widespread herb in Ayurveda that is said to enhance youth, longevity, and general well-being. Additionally, it is a potent aphrodisiac herb that supports and enhances healthy sexual function. This review will address the function of herbal remedies in male infertility and offer a thorough analysis of the numerous Withania somnifera related human and animal research that have been conducted explaining a potential direct oxidative mechanism that would reduce oxidative stress and an indirect mechanism that would enhance male fertility by modifying hormone balance through the interaction of many endocrine glands through the gamma-aminobutyric acid-like mimic pathway.